The Black Array of Broadband Absolute Radiometers Earth Radiation Imager: Science Requirements, Instrument Design, and Concept of Operations - Odele Coddington; Cameron Straatsma; Ginger Drake; Kush Tyagi; Michelle Stephens; Chris Yung; Nathan Tomlin; John Lehman; Chip Bollendonk; Paris Buedel; Katherine Catani; Beth Cervelli; et al. (Advances in Atmospheric Sciences, 2026)
The Black Array of Broadband Absolute Radiometers Earth Radiation Imager (BABAR-ERI) is a small, adaptable nadir-pointed pushbroom imager to measure Earth-leaving broadband radiance from 0.3 µm to 100 µm with higher information content than is currently measured by reducing radiometric uncertainty and enabling cloud-resolving spatial resolution. The three-instrument BABAR-ERI suite fits a 12U CubeSat form factor and contains co-registered science telescope channels for measuring shortwave (0.3 µm to 4.5 µm band) and total radiance (0.3 µm to 100 µm band), dual-channel on-board radiance stability monitors, and a visible-wavelength camera. Novel, 1 × 32 element, electrical-substitution radiometer pixels image the shortwave and total radiance in 1 km × 1 km co-registered ground footprints; longwave radiance (4.5 µm to 100 µm band) is derived from subtraction of the shortwave and total radiance. The dual-channel onboard stability monitors are radiance standard detectors, and their measurements, acquired concurrently with the science telescopes and at much different duty cycles for the dual channels, will be used to track and correct the degradation of the science channels. The single-channel, mid-visible camera facilitates geolocation pointing knowledge and provides scene context information and sub-pixel variability to facilitate measurement stability studies and enable process-level science studies at high spatial resolution. The detectors for the science channels and stability monitors are absolute, ambient-temperature, micro-fabricated, electrical-substitution radiometers with near-perfect optical absorptance across the measurement range from vertically aligned carbon nanotubes. The BABAR-ERI science channels will be characterized over the full measurement range and for variable Earth scenes and deep space temperatures during extensive ground calibrations.

Advancing the Implementation of Coastal Restoration in Louisiana Through a Co-production of Science Framework - Jacob M. Oster; Jessica R. Henkel; Alyssa Dausman; Eva D. Windhoffer; Bingqing Liu; Melissa M. Baustian; Denise Reed; Summer Langlois; David C. Lindquist (Estuaries and Coasts, 2025)
Coastal Louisiana faces complex challenges from the compounding effects of coastal land loss and climate change. The State of Louisiana’s Coastal Protection and Restoration Authority (CPRA) and the RESTORE Act Center of Excellence for Louisiana (LA-COE) have adopted a co-production of science framework to help ensure that scientific research funded through the LA-COE supports the research needs of CPRA and the Louisiana Coastal Master Plan (CMP), a large-scale coastal restoration plan that outlines activities needed to restore and protect Louisiana’s coast. In this paper, we describe the co-production of science framework established between the LA-COE, CPRA, and research projects funded by the LA-COE. Through an iterative process, the Louisiana CMP is revised every 6 years with improved model and scientific information. The LA-COE leverages the cyclical nature of the CMP by working with CPRA to identify research needs for each Request for Proposals solicited by the LA-COE. The LA-COE proposal review process is structured to include anonymous CPRA review of projects to promote the production of actionable science, and once funded, multiple mechanisms are in place to support collaboration between researchers and CPRA staff. We highlight these mechanisms and provide examples of four LA-COE-funded projects where co-produced science is being used by CPRA to inform the CMP and its implementation. Finally, we discuss challenges of co-production within the confines of funding requirements and review restrictions, highlighting how the LA-COE continues to adapt to navigate these challenges and enhance the implementation of co-production throughout the research funding lifecycle.

Broad‐scale climate patterns combined with local flow and turbidity disturbances structure the seasonality of gross primary production in an aridland river - Betsy M. Summers; Robert O. Hall; Justin K. Reale; Eric Joseph; Mark C. Stone; David J. Van Horn (Limnology and Oceanography, 2025)
Both local and global climate phenomena shape the hydrologic regimes of watersheds. For aridland rivers in the southwestern United States, peak flows occur during two distinct periods: spring snowmelt and summer monsoons. Although discharge ( Q ) is a primary driver of variation in the production and consumption of instream organic matter, or stream metabolism, few connection have been made regarding how climate impacts ecosystem processes through changes in flow and related disturbances. We considered how variation in disturbance variables, specifically Q and associated changes in turbidity, affected gross primary production during spring snowmelt and summer monsoons in the Rio Grande. Nine years of continuous environmental data ( Q , turbidity, light) and climate indices (i.e., El Niño‐Southern Oscillation and Monsoon Index) were used to explain the variation in gross primary production estimates. We found that relationships were sensitive to the timescale of disturbance: at the seasonal scale, high snowmelt Q decreased spring mean gross primary production, while at the daily scale, high turbidity, and to a lesser extent Q , reduced gross primary production during summer. Also, mean Q and turbidity disturbances were uncoupled in spring and inversely related in summer. We conclude that long‐term datasets are essential to uncover emergent relationships between broad‐scale climate patterns and ecosystem processes and are necessary to better understand how hydroclimatic variability drives ecosystem processes at varying time scales in rivers across Earth.

Near-infrared induced photothermal lateral-flow immunoassay utilizing plasmonics-active gold nanostars - Supriya Atta; Yuanhao Zhao; Sebastian Sanchez; Sabina V. Yampolsky; Vanessa K. Berner; Marcellene A. Gates-Hollingsworth; Jasmine Pramila Devadhasan; Alexander Jarrett Summers; Jian Gu; Douglas C. Montgomery; David P. AuCoin; Frederic Zenhausern; et al. (Analytica Chimica Acta, 2025)

Sublethal 6PPD-quinone exposure impairs swimming performance and aerobic metabolism in juvenile lake trout (Salvelinus namaycush) - Summer Selinger; Blake Hunnie; Catherine Roberts; Mawuli Amekor; Natacha Hogan; Steve Wiseman; Markus Hecker; Lynn Weber; David Janz; Markus Brinkmann (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Cryptic anatomical adaptive peak shifts and transitions along the body elongation continuum in zoarcoid fishes - Summer E. Duba; David C. Collar (Zoology, 2025)

Environmental exposure assessment in the international prospective study of Chronic Kidney Disease of UnceRtain Etiology (CKDu) in Agricultural Communities (CURE) research consortium: Design and protocol development - Marvin González-Quiroz; Anna Aceituno; Shuchi Anand; Alexander van Geen; Lawrence S. Engel; Emmanuel Jarquin; Clemens Ruepert; Nicole Villegas-González; Mariela Arias-Hidalgo; Nora Franceschini; Daylin Anchía-Pastrán; Karla Solano-Diaz; et al. (Science of The Total Environment, 2025)

Carbon farming co-benefits optimization in south-eastern Australian rangeland - Yuan Gao; Jeffery Connor; David Summers; Li Luo; Cathy Waters; Annette Cowie (Journal of Environmental Management, 2025)

Noise results in lower quality of an important forage fish, the Pacific sand lance, Ammodytes personatus - Nora V. Carlson; Meredith A.V. White; Jose Tavera; Patrick D. O'Hara; Matthew R. Baker; Douglas F. Bertram; Adam Summers; David A. Fifield; Francis Juanes (Marine Pollution Bulletin, 2025)

Acute cardiorespiratory effects of 6PPD-quinone on juvenile rainbow trout (Oncorhynchus mykiss) and arctic char (Salvelinus alpinus) - Summer J. Selinger; David Montgomery; Steve Wiseman; Markus Hecker; Lynn Weber; Markus Brinkmann; David Janz (Aquatic Toxicology, 2025)

Can Australian plantation forest carbon offset methods increase carbon storage and timber supply? A case study from the Green Triangle plantation forestry region in Australia - Courtney M. Regan; Jeffery D. Connor; David M. Summers; Will Mackay; Yuan Gao (Journal of Environmental Management, 2024)

Genome‐wide population affinities and signatures of adaptation in hydruntines, sussemiones and Asian wild asses - Jianfei Pan; Xuexue Liu; Mateusz Baca; Laure Calvière‐Tonasso; Stéphanie Schiavinato; Loreleï Chauvey; Gaétan Tressières; Aude Perdereau; Jean‐Marc Aury; Pedro H. Oliveira; Patrick Wincker; Aida Abdykanova; et al. (Molecular Ecology, 2024)
The extremely rich palaeontological record of the horse family, also known as equids, has provided many examples of macroevolutionary change over the last ~55 Mya. This family is also one of the most documented at the palaeogenomic level, with hundreds of ancient genomes sequenced. While these data have advanced understanding of the domestication history of horses and donkeys, the palaeogenomic record of other equids remains limited. In this study, we have generated genome‐wide data for 25 ancient equid specimens spanning over 44 Ky and spread across Anatolia, the Caucasus, Central Asia and Mongolia. Our dataset includes the genomes from two extinct species, the European wild ass, Equus hydruntinus , and the sussemione Equus ovodovi . We document, for the first time, the presence of sussemiones in Mongolia and their survival around ~3.9 Kya, a finding that should be considered when discussing the timing of the first arrival of the domestic horse in the region. We also identify strong spatial differentiation within the historical ecological range of Asian wild asses, Equus hemionus , and incomplete reproductive isolation in several groups yet considered as different species. Finally, we find common selection signatures at ANTXR2 gene in European, Asian and African wild asses. This locus, which encodes a receptor for bacterial toxins, shows no selection signal in E. ovodovi , but a 5.4‐kb deletion within intron 7. Whether such genetic modifications played any role in the sussemione extinction remains unknown.

The relationship between extreme inter-individual variation in macrophage gene expression and genetic susceptibility to inflammatory bowel disease - Claire L. O’Brien; Kim M. Summers; Natalia M. Martin; Dylan Carter-Cusack; Yuanhao Yang; Rasel Barua; Ojas V. A. Dixit; David A. Hume; Paul Pavli (Human Genetics, 2024)
The differentiation of resident intestinal macrophages from blood monocytes depends upon signals from the macrophage colony-stimulating factor receptor (CSF1R). Analysis of genome-wide association studies (GWAS) indicates that dysregulation of macrophage differentiation and response to microorganisms contributes to susceptibility to chronic inflammatory bowel disease (IBD). Here, we analyzed transcriptomic variation in monocyte-derived macrophages (MDM) from affected and unaffected sib pairs/trios from 22 IBD families and 6 healthy controls. Transcriptional network analysis of the data revealed no overall or inter-sib distinction between affected and unaffected individuals in basal gene expression or the temporal response to lipopolysaccharide (LPS). However, the basal or LPS-inducible expression of individual genes varied independently by as much as 100-fold between subjects. Extreme independent variation in the expression of pairs of HLA-associated transcripts ( HLA-B/C, HLA-A/F and HLA-DRB1/DRB5 ) in macrophages was associated with HLA genotype. Correlation analysis indicated the downstream impacts of variation in the immediate early response to LPS. For example, variation in early expression of IL1B was significantly associated with local SNV genotype and with subsequent peak expression of target genes including IL23A, CXCL1, CXCL3, CXCL8 and NLRP3 . Similarly, variation in early IFNB1 expression was correlated with subsequent expression of IFN target genes. Our results support the view that gene-specific dysregulation in macrophage adaptation to the intestinal milieu is associated with genetic susceptibility to IBD.

Emissions offset incentives, carbon storage and profit optimization for Australian timber plantations - Li Luo; Yuan Gao; Courtney M. Regan; David M. Summers; Jeffery D. Connor; Jim O'Hehir; Li Meng; Christopher W.K. Chow (Forest Policy and Economics, 2024)

Soil CO2 in organic and no-till agroecosystems - Summer R.A. Lockhart; C. Kent Keller; R. David Evans; Lynne A. Carpenter-Boggs; David R. Huggins (Agriculture, Ecosystems & Environment, 2023)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Correction to: Imaging tools for assessment of myocardial fibrosis in humans: the need for greater detail - Summer Hassan; Carolyn J Barrett; David J Crossman (Biophysical Reviews, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Current carbon prices do not stack up to much land use change, despite bundled ecosystem service co‐benefits - David M. Summers; Courtney M. Regan; Claire Settre; Jeffery D. Connor; Patrick O’Connor; Hayley Abbott; Jacqueline Frizenschaf; Leon van der Linden; Andrew Lowe; Katja Hogendoorn; Scott Groom; Timothy R. Cavagnaro (Global Change Biology, 2021)
Biological sources of carbon sequestration such as revegetation have been highlighted as important avenues to combat climate change and meet global targets by the global community including the Paris Climate Agreement. However, current and projected carbon prices present a considerable barrier to broad‐scale adoption of tree planting as a key mitigation strategy. One avenue to provide additional economic and environmental incentives to encourage wider adoption of revegetation is the bundling or stacking of additional co‐beneficial ecosystem services that can be realized from tree planting. Using the World's largest land‐based carbon credit trading scheme, the Australian Emissions Reduction Scheme (ERF), we examine the potential for three pairs of ecosystem services, where the carbon sequestration value of land use change is paired with an additional co‐benefit with strong prospects for local tangible benefits to land owners/providers. Two cases consider agricultural provisioning values that can be realized by the landowners in higher returns: increased pollination services and reduced lamb mortality. The third case examined payments for tree plantings along riparian buffers, with payments to farmers by a water utility who realizes the benefit from reduced treatment cost due to water quality improvements. Economic incentives from these co‐benefit case studies were found to be mixed, with avoided treatment costs from water quality paired with carbon payments the most promising, while pollination and reduced lamb mortality paired with carbon payments were unable to bridge the economic gap except under the most optimistic assumptions. We conclude that the economics case for significant land use change are likely to be geographically dispersed and only viable in relatively niche landscape positions in high establishment, high opportunity cost areas even when carbon payments are augmented with the value of co‐benefits classified as providing direct and local benefits.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Exploring movement patterns and changing distributions of baleen whales in the western North Atlantic using a decade of passive acoustic data - Genevieve E. Davis; Mark F. Baumgartner; Peter J. Corkeron; Joel Bell; Catherine Berchok; Julianne M. Bonnell; Jacqueline Bort Thornton; Solange Brault; Gary A. Buchanan; Danielle M. Cholewiak; Christopher W. Clark; Julien Delarue; et al. (Global Change Biology, 2020)
Six baleen whale species are found in the temperate western North Atlantic Ocean, with limited information existing on the distribution and movement patterns for most. There is mounting evidence of distributional shifts in many species, including marine mammals, likely because of climate‐driven changes in ocean temperature and circulation. Previous acoustic studies examined the occurrence of minke ( Balaenoptera acutorostrata ) and North Atlantic right whales (NARW; Eubalaena glacialis ). This study assesses the acoustic presence of humpback ( Megaptera novaeangliae ), sei ( B. borealis ), fin ( B. physalus ), and blue whales ( B. musculus ) over a decade, based on daily detections of their vocalizations. Data collected from 2004 to 2014 on 281 bottom‐mounted recorders, totaling 35,033 days, were processed using automated detection software and screened for each species' presence. A published study on NARW acoustics revealed significant changes in occurrence patterns between the periods of 2004–2010 and 2011–2014; therefore, these same time periods were examined here. All four species were present from the Southeast United States to Greenland; humpback whales were also present in the Caribbean. All species occurred throughout all regions in the winter, suggesting that baleen whales are widely distributed during these months. Each of the species showed significant changes in acoustic occurrence after 2010. Similar to NARWs, sei whales had higher acoustic occurrence in mid‐Atlantic regions after 2010. Fin, blue, and sei whales were more frequently detected in the northern latitudes of the study area after 2010. Despite this general northward shift, all four species were detected less on the Scotian Shelf area after 2010, matching documented shifts in prey availability in this region. A decade of acoustic observations have shown important distributional changes over the range of baleen whales, mirroring known climatic shifts and identifying new habitats that will require further protection from anthropogenic threats like fixed fishing gear, shipping, and noise pollution.

Imaging tools for assessment of myocardial fibrosis in humans: the need for greater detail - Summer Hassan; Carolyn J Barrett; David J Crossman (Biophysical Reviews, 2020)

What is marine justice? - Jennifer A. Martin; Summer Gray; Eréndira Aceves-Bueno; Peter Alagona; Tammy L. Elwell; Angela Garcia; Zach Horton; David Lopez-Carr; Jessica Marter-Kenyon; Karly Marie Miller; Christopher Severen; Teresa Shewry; et al. (Journal of Environmental Studies and Sciences, 2019)

Regional engagement and spatial modelling for natural resource management planning - Wayne S. Meyer; Brett A. Bryan; David M. Summers; Greg Lyle; Sam Wells; Josie McLean; Mark Siebentritt (Sustainability Science, 2016)

Fit-for-purpose phosphorus management: do riparian buffers qualify in catchments with sandy soils? - David Weaver; Robert Summers (Environmental Monitoring and Assessment, 2014)

Effect of cryotherapy on muscle recovery and inflammation following a bout of damaging exercise - Naomi J. Crystal; David H. Townson; Summer B. Cook; Dain P. LaRoche (European Journal of Applied Physiology, 2013)

Species vulnerability to climate change: impacts on spatial conservation priorities and species representation - David M. Summers; Brett A. Bryan; Neville D. Crossman; Wayne S. Meyer (Global Change Biology, 2012)

Species vulnerability to climate change: impacts on spatial conservation priorities and species representation - David M. Summers; Brett A. Bryan; Neville D. Crossman; Wayne S. Meyer (Global Change Biology, 2012)
Climate change may shrink and/or shift plant species ranges thereby increasing their vulnerability and requiring targeted conservation to facilitate adaptation. We quantified the vulnerability to climate change of plant species based on exposure, sensitivity and adaptive capacity and assessed the effects of including these components in complementarity‐based spatial conservation prioritisation. We modelled the vulnerability of 584 native plant species under three climate change scenarios in an 11.9 million hectare fragmented agricultural region in southern Australia. We represented exposure as species' geographical range under each climate change scenario as quantified using species distribution models. We calculated sensitivity as a function of the impact of climate change on species' geographical ranges. Using a dispersal kernel, we quantified adaptive capacity as species' ability to migrate to new geographical ranges under each climate change scenario. Using Zonation , we assessed the impact of individual components of vulnerability (exposure, sensitivity and adaptive capacity) on spatial conservation priorities and levels of species representation in priority areas under each climate change scenario. The full vulnerability framework proved an effective basis for identifying spatial conservation priorities under climate change. Including different dimensions of vulnerability had significant implications for spatial conservation priorities. Incorporating adaptive capacity increased the level of representation of most species. However, prioritising sensitive species reduced the representation of other species. We conclude that whilst taking an integrated approach to mitigating species vulnerability to climate change can ensure sensitive species are well‐represented in a conservation network, this can come at the cost of reduced representation of other species. Conservation planning decisions aimed at reducing species vulnerability to climate change need to be made in full cognisance of the sensitivity of spatial conservation priorities to individual components of vulnerability, and the trade‐offs associated with focussing on sensitive species.

Carbon Payments and Low‐Cost Conservation - NEVILLE D. CROSSMAN; BRETT A. BRYAN; DAVID M. SUMMERS (Conservation Biology, 2011)
A price on carbon is expected to generate demand for carbon offset schemes. This demand could drive investment in tree‐based monocultures that provide higher carbon yields than diverse plantings of native tree and shrub species, which sequester less carbon but provide greater variation in vegetation structure and composition. Economic instruments such as species conservation banking, the creation and trading of credits that represent biological‐diversity values on private land, could close the financial gap between monocultures and more diverse plantings by providing payments to individuals who plant diverse species in locations that contribute to conservation and restoration goals. We studied a highly modified agricultural system in southern Australia that is typical of many temperate agriculture zones globally (i.e., has a high proportion of endangered species, high levels of habitat fragmentation, and presence of non‐native species). We quantified the economic returns from agriculture and from carbon plantings (monoculture and mixed tree and shrubs) under six carbon‐price scenarios. We also identified high‐priority locations for restoration of cleared landscapes with mixed tree and shrub carbon plantings. Depending on the price of carbon, direct annual payments to landowners of AU$7/ha/year to $125/ha/year (US$6–120/ha/year) may be sufficient to augment economic returns from a carbon market and encourage tree plantings that contribute more to the restoration of natural systems and endangered species habitats than monocultures. Thus, areas of high priority for conservation and restoration may be restored relatively cheaply in the presence of a carbon market. Overall, however, less carbon is sequestered by mixed native tree and shrub plantings.